Small lesion size measured by colposcopy may predict absence of cervical intraepithelial neoplasia in a large loop excision of the transformation zone specimen. (9th August 2016) - Munmany, M; Marimon, L; Cardona, M; Nonell, R; Juiz, M; Astudillo, R; Ordi, J; Torné, A; del Pino, M
Abstract : Objective: To evaluate whether colposcopic measurement of the lesion size at diagnosis and/or human papillomavirus (HPV) genotyping can predict the absence of dysplasia in a large loop excision of the transformation zone (LLETZ) specimen in women treated for squamous intraepithelial lesions/cervical intraepithelial neoplasia (SIL/CIN). Design: Prospective observational study. Setting: Tertiary university hospital. Population: A cohort of 116 women who underwent LLETZ because of biopsy‐proven low‐grade SIL/CIN that had persisted for 2 years, or because of a high‐grade SIL/CIN diagnosed in the referral visit and squamocolumnar junction completely visible (types 1 or 2, according to the International Federation of Cervical Pathology and Colposcopy, IFCPC). Methods: After LLETZ the women were classified by histology into the study group (absence of SIL/CIN in the surgical specimen, 28/116, 24.1%) and the control group (SIL/CIN in the LLETZ specimen, 88/116, 75.9%). Main outcome measures: The size of the lesion determined in the diagnostic colposcopy and the HPV genotype were evaluated in all women. Results: The lesion size was significantly smaller in the study group (25.7 ± 37.8 versus 84.5 ± 81.7 mm 2 ; P < 0.001). A lesion size of ≤12 mm 2 and HPV types other than 16 or 18 were associated with an absence of SIL/CIN in the LLETZ specimen ( P < 0.001 and P = 0.016, respectively). On multivariate analysis only a lesion size of ≤12 mm 2 predicted the absence of SIL/CIN (odds ratio, OR 10.6; 95% confidence interval, 95% CI 3.6–30.6; P < 0.001). A lesion size of ≤12 mm 2 had a specificity of 90.9% (95% CI 83.0–95.3%) and a negative predictive value of 86.0% (95% CI 77.5–91.6%) to predict the absence of SIL/CIN in the surgical specimen. Conclusions: Small lesion size in diagnostic colposcopy could predict the absence of SIL/CIN in the LLETZ specimen. Colposcopy measurement of lesion size prior to LLETZ may avoid unnecessary treatment. Tweetable abstract: Small lesion size in colposcopic evaluation might predict the absence of SIL/CIN in an LLETZ specimen. Tweetable abstract: Small lesion size in colposcopic evaluation might predict the absence of SIL/CIN in an LLETZ specimen.